2016
DOI: 10.1001/jamasurg.2015.4516
|View full text |Cite
|
Sign up to set email alerts
|

Nomograms to Predict Recurrence-Free and Overall Survival After Curative Resection of Adrenocortical Carcinoma

Abstract: IMPORTANCE Adrenocortical carcinoma (ACC) is a rare but aggressive endocrine tumor, and the prognostic factors associated with long-term outcomes after surgical resection remain poorly defined. OBJECTIVES To define clinicopathological variables associated with recurrence-free survival (RFS) and overall survival (OS) after curative surgical resection of ACC and to propose nomograms for individual risk prediction. DESIGN, SETTING, AND PARTICIPANTS Nomograms to predict RFS and OS after surgical resection of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
100
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(102 citation statements)
references
References 40 publications
2
100
0
Order By: Relevance
“…We also suggested the reliability of a risk calculator for the prediction of DFS and CSS. Many studies have indicated that a scoring system or nomogram predicts long-term survival after a gastectomy [2][3][4][5]18], and they did so by identifying postoperative clinicopathological factors. Only a few studies have evaluated preoperative prognostic factors for predicting long-term outcomes in patients with gastric cancer, such as the Modified Glasgow Prognostic Score, C-reactive protein-to-albumin ratio, blood neutrophil-to-lymphocyte ratio, lymphocyte-tomonocyte ratio, albumin-to-globulin ratio, and combination of hemoglobin, albumin, lymphocytes, and platelets [19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also suggested the reliability of a risk calculator for the prediction of DFS and CSS. Many studies have indicated that a scoring system or nomogram predicts long-term survival after a gastectomy [2][3][4][5]18], and they did so by identifying postoperative clinicopathological factors. Only a few studies have evaluated preoperative prognostic factors for predicting long-term outcomes in patients with gastric cancer, such as the Modified Glasgow Prognostic Score, C-reactive protein-to-albumin ratio, blood neutrophil-to-lymphocyte ratio, lymphocyte-tomonocyte ratio, albumin-to-globulin ratio, and combination of hemoglobin, albumin, lymphocytes, and platelets [19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the prediction of long-term outcomes preoperatively is required for each patient. Some predictive factors of long-term prognosis after a gastrectomy have been reported [2][3][4][5]; however, only few studies have predicted long-term outcomes based on preoperative parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The authors also showed that adrenocortical carcinoma (ACC) was more common in younger patients compared to those patients with benign adenomas (median age 46 years versus 57 years). Due to the aggressive nature and rapid growth rate of ACC, and since achieving free margins is one of the most important determinants in extending patient survival [6,7], current guidelines suggest adrenalectomy in all surgically it patients with an adrenal mass >4 cm [8,9]. lipid concentration and low density.…”
Section: Imaging Characteristicsmentioning
confidence: 99%
“…Nomogram could evaluate the survival probability of patients with the speci c scoring system [13,14]. And nomograms have been used in different cancers for predicting survival rate [15,16]. Few studies used the nomograms to predict the survival rate of patients with advanced or metastatic PC [17,18].…”
Section: Introductionmentioning
confidence: 99%